2015
DOI: 10.1007/s13679-015-0152-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Obesity: A Plausible Explanation for Obesity

Abstract: Obesity is a multifactorial disorder that results in excessive accumulation of adipose tissue. Although obesity is caused by alterations in the energy consumption/expenditure balance, the factors promoting this disequilibrium are incompletely understood. The rapid development of new technologies and analysis strategies to decode the gut microbiota composition and metabolic pathways has opened a door into the complexity of the guest-host interactions between the gut microbiota and its human host in health and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(112 citation statements)
references
References 130 publications
(163 reference statements)
4
97
0
6
Order By: Relevance
“…In addition to antibiotics, certain non-antibiotic drugs and/or common medications can alter gut microbial growth or elicit changes that may induce antibiotic resistance [8]. Gut microbial imbalances are also common in chronic diseases like diabetes [9,10], inflammatory bowel disease [11], and obesity [12], as well as in neurodegenerative disorders like Parkinson's disease (PD) [13][14][15] and multiple system atrophy (MSA) [16,17]. Gut microbiome changes in PD and MSA often parallel associated gastrointestinal (GI) hyperpermeability, constipation, and dysmotility.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antibiotics, certain non-antibiotic drugs and/or common medications can alter gut microbial growth or elicit changes that may induce antibiotic resistance [8]. Gut microbial imbalances are also common in chronic diseases like diabetes [9,10], inflammatory bowel disease [11], and obesity [12], as well as in neurodegenerative disorders like Parkinson's disease (PD) [13][14][15] and multiple system atrophy (MSA) [16,17]. Gut microbiome changes in PD and MSA often parallel associated gastrointestinal (GI) hyperpermeability, constipation, and dysmotility.…”
Section: Introductionmentioning
confidence: 99%
“…), metabolic syndrome, and obesity (Tilg and Kaser ; Sanmiguel et al . ; Economopoulos et al . ; Yang and Kweon ), protection of the gut microbiome from unintended effects of antibiotics becomes increasingly urgent.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic exposure inherently causes dysbiosis, a perturbation of the number and composition of the microbiota that affects normal microbial balance. Antibiotic use can result in antibiotic-associated diarrhoea (McFarland physiological states, including allergies (Trompette et al 2014), asthma (Arrieta et al 2015), autism (Hsiao et al 2013;Buffington et al 2016), cancer (Garrett 2015), diabetes (Livanos et al 2016;Pedersen et al 2016), recovery from neurological injury (Kigerl et al 2016), metabolic syndrome, and obesity (Tilg and Kaser 2011;Sanmiguel et al 2015;Economopoulos et al 2016;Yang and Kweon 2016), protection of the gut microbiome from unintended effects of antibiotics becomes increasingly urgent.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is thought to be secondary to increased harvesting of fatty acids due to obesogenic microbiota and digestion of certain polysaccharides that would be indigestible otherwise, 57 increased absorption of carbohydrates and fat by increasing the glucose transporters and fatty acid translocase on gut mucosa, 60 increased carbohydrate fermentation efficiency 56,61 and increased inflammation and gut permeability. 62 Human clinical trials investigating the association between obesity and the microbiome are less robust and less consistent than animal studies. 63 A Dutch study that included monozygotic twins showed similar microbiome profiles between the pairs, but twins who were discordant on body mass index showed an inverse correlation between some clusters of Clostridium diversity and body mass index.…”
Section: Microbiome and Ec Risk And Protective Factors Obesitymentioning
confidence: 99%